Attentional bias in depressive patients and the moderating effect of concurrent anxiety - Markela-Lerenc, Jaana; Kaiser, Stefan; Fiedler, Peter; Mundt, Christoph; Weisbrod, Matthias (Psychopathology, 2011)
Background: Most previous studies finding positive results in the emotional Stroop test did not control for concurrent anxiety symptoms. This study investigated depressive patients without comorbid anxiety disorders in order to clarify existing inconsistent findings. Furthermore, we examined the relationship between anxiety level and the emotional Stroop effect in patients and healthy subjects. Subjects and Methods: Twenty-three depressive patients without comorbid anxiety disorder and 27 healthy subjects performed a mixed computerized version of the emotional Stroop test (attentional bias test). We assessed the state and trait anxiety and examined its correlation with the emotional Stroop effect. Results: We failed to find evidence for attentional bias in the patients as measured by longer reaction times to the emotional stimuli. However, there was a positive correlation between state anxiety and attentional bias in depressed patients. On the other hand, in healthy subjects the trait anxiety correlated negatively with attentional bias. Conclusions: Attentional bias is not found in depressed patients if only patients without comorbid anxiety disorders are included. Furthermore, healthy subjects with high trait anxiety levels may be vulnerable to affective disorders because they use avoidance strategies when encountering negative information.